Analysis of Students' Misconceptions in Solving Mathematics Problems on Flat Construction Materials - La Ili (Green Publisher Indonesia, 2022)
This study aims to find out the misconceptions experienced by students in solving mathematical problems in the material of quadrilaterals in the fourth grade of SD Negeri 2 Biwinapada. This type of research is qualitative research. The subjects in this study were 3 fourth-grade students at SD Negeri 2 Biwinapada. Data collection techniques using tests and interviews. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that the misconceptions experienced by students include: 1) classificational misconceptions, namely a) not writing down what is known and asked or other elements needed to answer questions and b) errors in determining examples of rectangular shapes which are square or square long. 2) Correlational misconceptions, namely a) errors in representing the problem in the form of pictures, b) errors in applying the area value in the formula and c) making mistakes in applying the relationship between the formula used and the problems contained in the problem. 3) Theoretical misconceptions, namely errors in writing quadrilateral units, namely area (cm) and circumference (cm2).